MENGURAI ASPEK HUKUM KEWAJIBAN BERAGAMA/ MENGANUT KEPERCAYAAN DI INDONESIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 146/PUU-XXII/2024 - Huroiroh, Ernawati (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
Freedom of religion and belief is a human right guaranteed by the Indonesian Constitution, as enshrined in Article 28E paragraph (1) of the 1945 Constitution. This article examines the legal aspects of religious obligations in Indonesia following the Constitutional Court Decision No. 146/PUU-XXII/2024. The decision marks a significant milestone in safeguarding individual rights to religious identity without discrimination, particularly concerning the inclusion of religion in state administrative documents such as the Identity Card (KTP). Through a normative juridical approach, employing statutory and conceptual frameworks, this article analyzes the legal implications of the Constitutional Court’s ruling on administrative practices and the protection of citizens’ constitutional rights. The analysis reveals that the decision broadens the scope for the recognition of beliefs outside the six official religions and paves the way for more inclusive state policy reforms. In addition to establishing a new legal foundation, the ruling also triggers social dynamics and resistance from conservative groups. Therefore, the role of the state in harmonizing legal policies with the values of pluralism and tolerance becomes crucial in ensuring full religious freedom in Indonesia.